Do Trees on Farms Improve Household Well-Being? Evidence From National Panel Data in Uganda - Miller, Daniel C.; Muñoz-Mora, Juan Carlos; Rasmussen, Laura V.; Zezza, Alberto (Frontiers in Forests and Global Change, 2020)
Trees on farms provide livelihood benefits to households across Africa. To date, however, evidence on how such trees affect household wellbeing over time remains lacking. Evidence is especially sparse at the national level where it has particular value for policymaking. To address this knowledge gap, we use nationally-representative panel data from Uganda to examine how on-farm tree growing may affect two dimensions of household wellbeing: income and food security and nutrition. We analyzed household-level data from the 2005-06, 2010-11, and 2013-14 Ugandan National Panel Surveys, including measures on adoption and abandonment of trees on farms, demographic factors, and other socio-economic variables. We used a fixed-effect panel specification and probabilistic models to assess the relationship between the area devoted to trees on farms and household income and nutrition outcomes for 1395 households across Uganda. Our results suggest that having on trees on farms, especially fruit trees, is associated with improvements in both total household consumption and nutritional outcomes (measured by weight and wasting status of children under five). These findings suggest the important role trees on farms can play in poverty reduction and sustainable development efforts in Uganda and other countries in Africa and beyond.